STRATEGY IN IMPROVING THE QUALITY OF GRADUATES THROUGH AUTHENTIC ASSESSMENT MANAGEMENT IN SENIOR HIGH SCHOOL - M Khoirul Fahmi (Jurnal Isema : Islamic Educational Management, 2022)
This study explores how management team of SMAN 9 Malang improves the quality of graduates, especially how quality of graduates have created from some innovations of educational evaluation. Adopting the qualitative research design, the study presented in this paper ascertained the implementation of Management of Authentic Assessment in SMAN 9 Malang, integrated coordination system in authentic assessment management of education, and implications of authentic assessment management on the quality of graduates in SMAN 9 Malang. By using the innovative design of authentic assessment management program. it can make all of teachers easily to teach and evaluate their student with E-Front application, also there is an integrated coordination system in authentic assessment management of education namely ManJadda Wajada, and SMAN 9 Malang develops an online learning namely E-Fornt that connect with E-Raport as student marks data, and unforgettable these all happened because of collaboration system between ministry of education and management team of SMAN 9 Malang.